2005
DOI: 10.1063/1.1897830
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum nanoscale order in amorphous Al92Sm8 measured by fluctuation electron microscopy

Abstract: When annealed below T g , the melt-spun material exhibits a steadily decreasing nucleation rate, 4 which suggests heterogeneous nucleation. 5 The nucleation site has so far eluded structural or chemical detection, ruling out common sites like second phase interfaces or large impurity clusters. This suggests that the nucleation sites in quenched Al 92 Sm 8 may be a form of nanometer-length structure or medium-range order ͑MRO͒. Such structure is difficult to detect in amorphous materials using conventional tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 21 publications
2
68
0
Order By: Relevance
“…Aluminum-like MRO was detected from a melt-spun Al 92 Sm 8 sample, whereas no Al-like order was detected from a sample amorphized by plastic deformation. [31] A small change in composition, such as adding a few percent of Ta into a Zr-Cu-Ni-Al alloy [32] [23] may change the MRO. It has also been found that the thinning method used to prepare the TEM sample may affect the MRO-ion thinning induces more structural order than electropolishing.…”
Section: Chalcogenide Glasses: Evolution Of Nuclei In Phase-change Mamentioning
confidence: 99%
“…Aluminum-like MRO was detected from a melt-spun Al 92 Sm 8 sample, whereas no Al-like order was detected from a sample amorphized by plastic deformation. [31] A small change in composition, such as adding a few percent of Ta into a Zr-Cu-Ni-Al alloy [32] [23] may change the MRO. It has also been found that the thinning method used to prepare the TEM sample may affect the MRO-ion thinning induces more structural order than electropolishing.…”
Section: Chalcogenide Glasses: Evolution Of Nuclei In Phase-change Mamentioning
confidence: 99%
“…The unique capability of MA is exemplified by several novel structures such as the extension of solid solubility in systems that are immiscible in equilibrium [2][3][4], the synthesis of metallic glass [5] and different kinetic pathways in solid solution formation [6]. These novel structures are not initiated by the usual thermally activated diffusion.…”
Section: Introductionmentioning
confidence: 98%
“…Heterogeneous nucleation requires a high density of nanoscale structural precursor sites to account for the large number of nucleation events. We have recently shown using fluctuation electron microscopy (FEM) that one amorphous Al alloy, Al 92 Sm 8 , contains nanoscale aluminum-like order, which may be that heterogeneous nucleation site [9].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, FEM was used to study amorphous semiconductors [10,15,16], but recently it has been used to study amorphous oxides [17,18], amorphous carbon films [19], and amorphous metals [9,20].…”
Section: Introductionmentioning
confidence: 99%